Lajes maciças pré-moldadas: diretrizes para padronização do projeto para produção - Silva, Rene Rodrigues Oliveira (2022)
The production of cast-in-situ slabs for residential buildings is considered a critical activity in relation to ergonomics and risk of accidents, in addition to being a production bottleneck, as it is a prerequisite for several other activities. Thus, many construction companies choose to produce the slabs of multifamily buildings in the standards of precast concrete at construction sites: Precast Solid Slabs (PSS). In this context, this work aims to propose guidelines for the standardization of a Design for Production of PSS, considering standardized panels with standard dimensions. The proposed guidelines were supported through action research involving three learning cycles in the execution of a multi-story building. At the end of each cycle, actions were proposed to solve the detected problems, and their implementation in the following cycle, constituting continuous and cumulative learning. The guidelines address the stages of production of PSS panels at the construction site and assembly on the floors. The executive details of the production processes, lifting devices, installation niches, connections between panels and the design of a customizable formwork system are indicated. The Design for Production will contribute to the increase in industrialization in the construction of residential works, which usually use cast-in-place slabs.